People in a sea of grass : archaeology's changing perspective on indigenous Plains communities - Hill, Matthew E., Jr. (Matthew Ervin); Ritterbush, Lauren W. (Lauren Walker) (University of Utah Press, 2022)
"This project outlines the current understanding of the last 2000 years of central Plains archaeology using a historical perspective. The volume authors describe how this knowledge has grown from data collected over the past century, or has changed based on critiques or modifications of these earlier studies. They also present new theoretical perspectives and methodologies which led them to accept, reject or revamp prior archeological interpretations. The volume was initially started as a conference symposium to recognize the long-term contributions of founding Plains archaeologist Waldo Wedel. The purpose was to present current work based on either the continuation, modification, or rejection of earlier archaeological findings about central Plains cultures"--